Avascular necrosis in a HIV patient receiving ritonavir and inhaled fluticasone. (May 2014) - Pollett, S; Graves, B; Richards, B; MacLeod, C
We report a case of severe bilateral knee avascular necrosis in a HIV-positive man receiving ritonavir and inhaled fluticasone. This case highlights the need for a thorough medication history in patients on ritonavir-based antiretroviral therapy, especially where multiple prescribers are involved in the patient's care.